Diverse endogenous antigens for mouse NKT cells: self-antigens that are not glycosphingolipids. - Pei, B; Speak, A; Shepherd, D; Butters, T; Cerundolo, V; Platt, F; Kronenberg, M (2011)
NKT cells with an invariant Ag receptor (iNKT cells) represent a highly conserved and unique subset of T lymphocytes having properties of innate and adaptive immune cells. They have been reported to regulate a variety of immune responses, including the response to cancers and the development of autoimmunity. The development and activation of iNKT cells is dependent on self-Ags presented by the CD1d Ag-presenting molecule. It is widely believed that these self-Ags are glycosphingolipids (GSLs), molecules that contain ceramide as the lipid backbone. In this study, we used a variety of methods to show that mammalian Ags for mouse iNKT cells need not be GSLs, including the use of cell lines deficient in GSL biosynthesis and an inhibitor of GSL biosynthesis. Presentation of these Ags required the expression of CD1d molecules that could traffic to late endosomes, the site where self-Ag is acquired. Extracts of APCs contain a self-Ag that could stimulate iNKT cells when added to plates coated with soluble, rCD1d molecules. The Ag(s) in these extracts are resistant to sphingolipid-specific hydrolase digestion, consistent with the results using live APCs. Lyosphosphatidylcholine, a potential self-Ag that activated human iNKT cell lines, did not activate mouse iNKT cell hybridomas. Our data indicate that there may be more than one type of self-Ag for iNKT cells, that the self-Ags comparing mouse and human may not be conserved, and that the search to identify these molecules should not be confined to GSLs.